Effect of the dynamics of human behavior on the competitive spreading of information. (December 2018) - Yan, Xiangbin; Jiang, Ping
Abstract: In the current online environment, it is very common to have many different kinds of information spreading concurrently on social media. This study investigates the competitive spreading phenomenon by comparing positive information and negative information. Using a dynamical systems approach, we propose an information competition model to explore the competitive results. The model reveals what kind of information will win the aforementioned competition by describing the dynamic changes of the number of information spreaders. Dynamic analysis and simulation results of the model show that a group in a competitive spreading system cannot absolutely win, whether this group spreads positive information or negative information. The reason is that the group influence plays a more important role than the negativity bias in the process of competitive information diffusion. The existence of group influence aggravates people's herd psychology. People are more willing to believe and follow the behavior of the majority. This study not only enriches the information spreading model, but can also be used to guide emergency management and online marketing decisions. Highlights: We model the competition between positive information and negative information. Theoretical analysis indicates that competition results among messages may waver. Group influence is more important than negativity bias in information competition. This study provides useful advice for emergency management and online marketing.